Technology Innovation Project. Participatory evaluation on the introduction of leguminous cover crops in slash and mulch systems for sustainable corn production in the Toledo District, Belize - Instituto Interamericano de Cooperación para la Agricultura (IICA) (IICA, 2021)
Posee anexos y cuadros.